Can y= 6x^2-13x-5 y=6x2−13x−5 be factored? If so what are the factors ? Algebra Polynomials and Factoring Monomial Factors of Polynomials 1 Answer P dilip_k Mar 12, 2016 =>(2x-5)(3x+1)⇒(2x−5)(3x+1) Explanation: 6x^2-13x-56x2−13x−5 =>6x^2-15x+2x-5⇒6x2−15x+2x−5 =>3x(2x-5)+1(2x-5)⇒3x(2x−5)+1(2x−5) =>(2x-5)(3x+1)⇒(2x−5)(3x+1) Answer link Related questions What are Monomial Factors of Polynomials? How do you factor polynomials by finding the greatest common factor? How can a factoring problem be checked? How do you find the greatest common factors of variable expressions? How do you factor 3a+9b+63a+9b+6? What is the greatest common factor of a^3-3a^2+4aa3−3a2+4a? How do you factor 12xy+24xy^2+36xy^312xy+24xy2+36xy3? How do you find the greatest common factor of 45y^{12}+30y^{10}45y12+30y10? How do you factor 92x^10y^4 - 54x^12y^992x10y4−54x12y9? How do you factor 4x^2+x4x2+x? See all questions in Monomial Factors of Polynomials Impact of this question 1625 views around the world You can reuse this answer Creative Commons License